Monitoring of development resistance of aphids (Schizaphis graminum Rond.) to drugs of different chemical groups - Berezovskaya-Brigas, V.; Secun, N. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The susceptibility of aphids to pyrethroid insecticides has been studied. The resistance index does not exceed 10. It is shown that when selecting the population by Decis Profi and Carte, the development of resistance in insects is accelerated in comparison with BI-58 New and Zolon.